Restoring Self-Image in the Light of Imago Dei for Addictive Substance Abusers in the Contemporary Era - Lase, Onesiporus Pengharapan; Parinussa, Stevanus (STT Transformasi Indonesia Manado, 2025)
Substance addiction in the contemporary era does not merely create a physical health crisis, but also severely damages the self-image and spiritual identity of the addicted individuals. Social stigma, deep-rooted guilt, and disconnection from God and community further worsen their psychosocial and spiritual condition. However, medical and psychological approaches that have so far dominated treatment often fail to address the core of the spiritual identity crisis. There is a clear research gap in theological studies that specifically examine self-image recovery through reflection on the Imago Dei within the context of addiction. From a theological perspective, restoring self-image is not merely a psychological reconstruction, but also a rediscovery of human identity grounded in the Imago Dei. This article explores how theological reflection on the Imago Dei offers a transformative approach in restoring the self-image of substance abusers. This study employs a qualitative approach using a descriptive design to gain an in-depth understanding of addiction cases and treatment. Data collection involved non-numerical sources using triangulation methods through pastoral interviews, counseling observations, and spiritual reflection analyses. The findings show that deep reflection on the Imago Dei fosters holistic transformation spiritually, psychologically, and sociall ywhich significantly contributes to a sustainable recovery process.